The effectiveness of chitosan-mediated silencing of PDGF-B and PDGFR-beta in the mesangial proliferative glomerulonephritis therapy - ÖZBAŞ, SUNA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
Platelet-derived growth factor-B (PDGF-B) is a growth factor that plays an important role in the progression of mesangial proliferative glomerulonephritis (MsPGN). PDGF-B may contribute to mesangioproliferative changes and is overexpressed in MsPGN. Recently, small interfering RNAs (siRNAs) have been widely used for gene silencing effects in experimental models of renal diseases. Nanoparticle-based therapeutics are preferred for reasons such as increasing therapeutic efficacy and reducing toxic effects caused by high doses. The distribution of nanoparticles to the kidney is a significant advantage in siRNA delivery. The aim of this study was to investigate the efficacy of chitosan/siRNA nanoplexes in silencing of PDGF-B and PDGFR-beta genes in kidney and to decrease mesangial cell proliferation and matrix accumulation in MsPGN model induced by anti-Thy-1.1 antibody. The therapeutic effects of chitosan/siPDGF-B + siPDGFR-beta nanoplexes in glomerulonephritic rats were studied by molecular, biochemical, and histopathologic evaluations. Chitosan/siPDGF-B + siPDGFR-beta nanoplexes markedly reduced PDGF-B and PDGFR-beta mRNA and protein expressions in experimental MsPGN model. Histopathologic examination results showed that the silencing of PDGF-B and its receptor PDGFR-beta led to reduction in mesangial cell proliferation and matrix accumulation. The use of chitosan/siPDGF-B + siPDGFR-beta nanoplexes for silencing the PDGF-B pathway in MsPGN can be considered as a new effective therapeutic strategy.
Keywords: MsPGN; PDGF-B; PDGFR-beta; siRNA; Chitosan; CHRONIC KIDNEY-DISEASE; CELL-PROLIFERATION; IN-VITRO; THY-1 NEPHRITIS; SIRNA; OLIGOSACCHARIDE; NANOPARTICLES; ANTIOXIDANT; PROTEINURIA; INHIBITION